MULTINATIONALS AND WAGES: EVIDENCE FROM EMPLOYER–EMPLOYEE DATA IN SERBIA - Delevic, Uros; Kennell, James (Economic Annals, 2022)
Many studies have reported that foreign-owned companies pay higher wages on average than domestic companies. However, this can be attributed to the different composition of the workforce or to a wage premium at the individual worker level. This paper contributes to this literature by observing whether individuals that change their job from a domestic to a foreign-owned company experience a change in their wages. Furthermore, it investigates whether this difference in wage patterns is moderated by workers’ education. This paper is one of the very few micro-econometric studies that deal with this question in a transition country, Serbia, using employer–employee data on the private sector over a long time period (15 years). Changing jobs is found to be positively associated with workers’ wages: the change in wages is higher when moving from a domestic to a foreign company than vice versa. The evidence suggests that more-educated workers benefit the most from leaving domestic companies.